Educational psychology manifestations in selected teen novels - Muhamad Affendi, Nik Rafidah Nik; Awang Pawi, Awang Azman; Roslan, Nur Widad; Mamat, Roslina; Md Zain, Rosnani (Human Resource Management Academic Research Society, 2022)
The transition from childhood to adolescence provides a variety of experiences, stress and emotional turmoil to adolescents, especially in school. This indirectly requires the adolescents to manage their psychological elements wisely. One of the psychological elements that should be applied by the author in teen novels is educational psychology. In general, educational psychology is a branch of knowledge that discusses human behavior during the teaching and learning process. Starting from the opinion of literary scholars who stated the appropriateness of educational psychology elements applied by authors of adolescent novels in order to form, encourage and increase motivation in the learning of adolescents to pursue and achieve goals in their lives. In this regard, this study classifies and analyzes the psychological elements of adolescence found in the novel Bening Mata Seorang Dia (2019) by Adnie Bahiah. The Social Learning Theory founded by Albert Bandura was used as a basis in this study. Discussion found three dominant factors that influence the educational psychology of adolescent, which are family, teacher and environmental factors.